Vitamin D deficiency and clinical severity of Covid-19 infection - Yucel, Hasan Esat; Erbesler, Zeynel Abidin; Tur, Kaan; Celiker, Mesut; Konar, Naime Meric; Ucar, Cahit (Annals of Medical Research, 2022)
Aim: Pancreatic ductal adenocarcinoma (PDAC) has high mortality and early stage metastatic potential. Thus, the developing new clinical approach and metastasis blocking strategy-based drugs are essential for cure of PDAC. In this study we aimed to investigate the effects of cell surface transmembrane glycoprotein CD44 on the regulation of key ECM proteins, integrin β1, fibronectin and collagen IV, in Panc-1 and MiaPaCa-2 cells. Material and Methods: Followed by cell viability assay using MTS, fibronectin and collagen IV protein expression levels and integrin β1 mRNA level were analyzed in Panc-1 and MiaPaCa-2 cells treated with 50 nM negative siRNA and CD44 siRNA for 72 h using western blot and RT-PCR, respectively. Results: Based on our findings, the downregulation of CD44 using specific siRNA led to decrease fibronectin and collagen IV proteins expressions, and also Integrin β1 mRNA expression in both Panc-1 and MiaPaCa-2 cell lines. Conclusion: CD44 siRNA based therapies have effective role to inhibit ECM degradation in PDAC progression. CD44 is also promising target for against PDAC through inhibiting migration, invasion and metastasis steps.
Keywords: Pancreatic ductal adenocarcinoma (PDAC); siRNA; extracellular matrix; metastasis